2012
DOI: 10.1039/c2dt30829k
|View full text |Cite
|
Sign up to set email alerts
|

Ru-based donor–acceptor photosensitizer that retards charge recombination in a p-type dye-sensitized solar cell

Abstract: We report on the synthesis and characterization of a donor-acceptor ruthenium polypyridyl complex as a photosensitizer for p-type dye-sensitized solar cells (DSSCs). The electrochemical, photophysical, and photovoltaic performance of two ruthenium-based photosensitizers were tested in NiO-based DSSCs; bis-(2,2'-bipyridine-4,4'-dicarboxylic acid)(2)N-(1,10-phenanthroline)-4-nitronaphthalene-1,8-dicarboximide ruthenium(II), ([Ru(dcb)(2)(NMI-phen)](PF(6))(2)) and tris-(2,2'-bipyridine-4,4'-dicarboxylic acid)(3) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 36 publications
(57 reference statements)
5
62
0
Order By: Relevance
“…8 Recently, significant improvements to NiO-based p-DSCs have been made by designing dyes which promote charge separation and limit the recombination between the sensitizer and/or electrolyte and the semiconductor. [9][10][11][12][13][14] Currents obtained in these devices have reached over 8 mA cm -2 at 1 sun illumination. 4,15 Earlier, we reported a high performance dye based on a triphenyl amine electron donor and a cationic indolium acceptor unit that absorbed in this region.…”
Section: Introductionmentioning
confidence: 88%
“…8 Recently, significant improvements to NiO-based p-DSCs have been made by designing dyes which promote charge separation and limit the recombination between the sensitizer and/or electrolyte and the semiconductor. [9][10][11][12][13][14] Currents obtained in these devices have reached over 8 mA cm -2 at 1 sun illumination. 4,15 Earlier, we reported a high performance dye based on a triphenyl amine electron donor and a cationic indolium acceptor unit that absorbed in this region.…”
Section: Introductionmentioning
confidence: 88%
“…5,6,9,44−46 In addition, we and others have previously demonstrated that such complexes were suitable photosensitizers to inject holes into NiO films for solar cells. 47,48 One bipyridine ligand of the ruthenium complex ([Ru((PO 3 H 2 CH 2 ) 2 bpy)(bpy) 2 ](PF 6 ) 2 ) was substituted with two methyl phosphonic acid groups in the 4,4′ positions to establish a strong and stable linkage with the NiO surface (see Scheme 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…[11][12][13][14] Owing to their remarkably stable photoredox chemistry, many ruthenium polypyridyl complexes are potent chromophores for lightdriven catalysis, [15,16] dye-sensitized solar cells, [17][18][19] and photocatalytic water splitting. [20,21] Crucial factors for their application herein are (1) high chemical stability, (2) intense absorption of visible light, (3) efficient population of a reactive charge-transfer (CT) excited state, and (4) long excitedstate lifetimes (up to the μs range).…”
Section: Introductionmentioning
confidence: 99%